Strategies of german car companies in china - Schrott, Patrick (Anchor Academic Publishing, 2014)
In 2009, the PRC overtook the USA as the biggest automotive market in the world in production as well as in sales. With economic problems like stagnating real income, rising raw material prices and credit-driven consumerism in the industrial countries the importance of the Chinese market for car companies will even grow. Saturated passenger car markets in the USA and Western Europe and low rates of motorization in new automotive markets like China focus the attention of the market participants on these new, growing markets. The focus of this study is on the passenger vehicle market and lines o.